PENGARUH LINGKUNGAN KERJA, KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA WISDOM WEALTH AGENCY DI KOTA BATAM.pdf - Sutrisno, Hendy; Wasiman (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine the effect of work environment, compensation and work motivation on job satisfaction at the Wisdom Wealth Agency. The sampling technique in this study is a saturated sampling technique with a population of 230 employees, so the number of samples taken is 230 respondents. Data was obtained through distributing questionnaires to Wisdom Wealth Agency employees. Data analysis was performed using multiple linear regression analysis. The data quality test in this study used the validity test and reliability test, the classical assumption test in this study used the normality test, multicollinearity test and heteroscedasticity test and the influence test used multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis test in this study using the t test and F test using the SPSS version 25 software program. The results show that the work environment has a significant effect on job satisfaction, compensation also has a significant effect on job satisfaction, and work motivation also has a significant effect on job satisfaction and work environment, compensation and work motivation together affect job satisfaction at the Wisdom Wealth Agency.